A safe haven of SARS-CoV-2 in the environment: prevalence and potential transmission risks in the effluent, sludge, and biosolids (2022)
The novel coronavirus, SARS-CoV-2, which has caused millions of death globally is recognized to be unstable and recalcitrant in the environment, especially in the way it has been evolving to form new and highly transmissible variants. Of particular concerns are human-environment interactions and the handling and reusing the environmental materials, such as effluents, sludge, or biosolids laden with the SARS-CoV-2 without adequate treatments, thereby suggesting potential transmission and health risks. This study assesses the prevalence of SARS-CoV-2 RNA in effluents, sludge, and biosolids. Further, we evaluate the environmental, ecological, and health risks of reusing these environmental materials by wastewater/sludge workers and farmers. A systematic review of literature from the Scopus database resulted in a total of 21 articles (11 for effluents, 8 for sludge, and 2 for biosolids) that met the criteria for meta-analysis, which are then subdivided into 30 meta-analyzed studies. The prevalence of SAR-CoV-2 RNA in effluent and sludge based on random-effect models are 27.51 and 1012.25, respectively, with a 95% CI between 6.14 and 48.89 for the effluent, and 104.78 and 1019.71 for the sludge. However, the prevalence of SARS-CoV-2 RNA in the biosolids based on the fixed-effect model is 30.59, with a 95% CI between 10.10 and 51.08. The prevalence of SARS-CoV-2 RNA in environmental materials indicates the inefficiency in some of the treatment systems currently deployed to inactivate and remove the novel virus, which could be a potential health risk concern to vulnerable wastewater workers in particular, and the environmental and ecological issues for the population at large. This timely review portends the associated risks in handling and reusing environmental materials without proper and adequate treatments.